Determinants of the sustainable internationalization and risk‐taking factors in public commercial banks. Issue 4 (1st February 2021) - Ashfaq, Saleha; Maqbool, Rashid; Rashid, Yahya
Abstract : Banking activities have crossed the border and spread worldwide. Internationalization is known as the need of the day for sustainability in height competitive banking sector trends. Is there any effect of internationalization on profitability to sustain in a competitive market or just increases risk factors? Here, the study investigates the need and effect of internationalization on bank risk in developing country like Pakistan by using seven public commercial banks' quarterly data that are being taken for the duration from 2007 to 2016. The study constructs hypotheses to justify the significance or insignificance relation of risk with internationalization variables and some other bank‐specific variables that independently affect the risk‐taking of internationalized banks. The main variables are Z ‐score for risk measurement and to evaluate the degree of internationalization. The study used foreign loan ratio and foreign income ratios. To support our work, the study also constructed some control variables like size, income diversification, and listed. We find that internationalization is associated with higher income earning in significant and positive relation with risk.